PENGARUH MEDIA KONKRET TERHADAP KEMAMPUAN NUMERASI AWAL SISWA SEKOLAH DASAR: STUDI EKSPERIMEN PADA PEMBELAJARAN PENJUMLAHAN DAN PENGURANGAN - Dethan, Endang Adolfina; Hingrida M. A. Hendrik; Radka Bodkova (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Early numeracy constitutes a fundamental competency that influences students’ future mathematical achievement. Nevertheless, many first-grade students experience difficulties in understanding addition and subtraction because mathematical concepts are often presented symbolically and abstractly. This study investigated the effect of concrete manipulatives on students’ numeracy skills in primary mathematics learning. The research employed a quantitative approach using a pre-experimental one-group pretest-posttest design. Participants consisted of 33 first-grade students of SDK Santo Yoseph 4 Kupang selected through total sampling. Data were collected using achievement tests measuring addition and subtraction skills. The findings revealed a substantial improvement in students’ performance after the intervention. The mean pretest score was 54.57, whereas the mean posttest score increased to 85.30. Paired-sample t-test analysis demonstrated a statistically significant difference between pretest and posttest scores (p < .001). The findings indicate that concrete manipulatives effectively facilitate conceptual understanding by transforming abstract mathematical symbols into observable and manipulable representations. The study contributes empirical evidence supporting constructivist and cognitive-developmental perspectives emphasizing the importance of hands-on learning experiences in early mathematics education. The integration of concrete media is therefore recommended as an instructional strategy to strengthen foundational numeracy competencies in lower primary classrooms.